Transport law science: interdisciplinary connections, promising directions of development - Khоtsko Olga A. (Journal of the Belarusian State University. Law, 2025)
The need to develop transport law has been investigated in view of a number of relevant aspects in legal science and practice. The task is to show the need to form a corresponding science on the formulation of the problem of insufficient development of transport law as a branch of legislation basis. It is revealed the relationship of the branches of law that is important for achieving significant goals of legal regulation of transport activities. Approaches to increase the level of systematicity and effectiveness of legal regulation in this area are considered. Areas that determine the improvement of legislation in the field of ensuring transport activities, in particular, related to determining the balance of public and private interests, the systematisation of norms in the relevant area, the deepening environmentalisation of transport legislation, taking into account the complexity of transport law for the search for the necessary legal means are studied.